Knight Owl - Denise, Christopher (New York Little, Brown and Company, 2022)
After achieving his dream of becoming a knight, a small owl protects the castle from a hungry dragon.
"Christy Ottaviano Books."
Ages 4-8.
111039
Keywords: Knights and knighthood -- Juvenile fiction; Owls -- Juvenile fiction; Dragons -- Juvenile fiction; Juvenile Fiction / General; Fiction; Juvenile works; Picture books; Livres d'images.; Children's stories -- Pictorial works